2008
DOI: 10.1007/s12289-008-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Precipitate Dissolution in Hardened Aluminium Alloys using Neural Networks

Abstract: This work presents a neural networks approach for finding the effective activation energy and modeling the dissolution rate of hardening precipitates in aluminium alloys using inverse analysis. As way of illustration, a class of multilayer perceptron extended with independent parameters is applied for that purpose to aluminium alloys AA-7449-T79, AA-2198-T8 and AA-6005A-T6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…proposed in the literature based on analytical expressions [122][123][124][125][126][127][128][129][130][131][132][133][134][135], as described in details in the review paper by Grong and Shercliff [13]. These analytical models use the Johnson-Mehl, Avrami, Kolmogorov (JMAK) formalism for the nucleation and growth of the precipitates and the Whelan formalism (i.e.…”
Section: Internal Variable Approach Many Models For Microstructure Ementioning
confidence: 99%
“…proposed in the literature based on analytical expressions [122][123][124][125][126][127][128][129][130][131][132][133][134][135], as described in details in the review paper by Grong and Shercliff [13]. These analytical models use the Johnson-Mehl, Avrami, Kolmogorov (JMAK) formalism for the nucleation and growth of the precipitates and the Whelan formalism (i.e.…”
Section: Internal Variable Approach Many Models For Microstructure Ementioning
confidence: 99%
“…In addition to these results, we have to point out that some improvements have been proposed in recent years to optimize the computation of the master curves and provide estimations of time evolution in precipitate fraction. More especially Lopez et al (2008) have developed a neural networks (NN) strategy to get both the effective activation energy and associated master curves related to precipitate dissolution stage. The aim of author was to model the dissolution rate of hardening precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…output). Quite complex expressions are proposed by Lopez et al (2008) as shown hereafter for AA-7449-T79, AA-2198-T8 and AA-6005A-T6 aluminium grades respectively where and denotes ( ⁄ ) and ⁄ quantities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…López et al and Agelet de Saracibar et al developed numerical algorithms to optimize material model and FSW process parameters using neural networks. They proposed a new model for the dissolution of precipitates in fully hardened aluminum alloys and they optimized the master curve and the effective activation energy.…”
Section: Introduction and State Of The Art In Fswmentioning
confidence: 99%